Investigations on thermal profiles and flow structures in a square channel equipped with staggered vortex turbulators - Boonloi, Amnart; Lewpiriyawong, Nuttawut; Jedsadaratanachai, Withada (My University, 2024)
Given the escalating energy demands today, improving the efficiency of engineering equipment is crucial for optimizing energy use. This study focuses on enhancing heat exchanger performance through passive methods, particularly by installing vortex turbulators. Passive techniques can effectively manage energy costs while enhancing efficiency. The research examines thermal profiles and airflow structures within a square channel heat exchanger (SCHE) equipped with staggered vortex turbulators (SVTs). SVTs feature a unique design combining rectangular winglets and V-pattern baffles. The installation of SVTs aims to intensify vortex strength, thereby increasing SCHE efficiency, convective heat transfer coefficients, and overall heat transfer potential. The study investigates the effects of SVT dimensions (b1/H and b2/H), airflow directions (+x and -x), installation patterns (pattern no. 1 and 2), pitch to height ratios (P/H = 1, 1.5, and 2), and flow attack angles (α = 20°, 30°, and 45°). Computational simulations using the finite volume method with a commercial code (FLUENT) under laminar flow conditions (Reynolds number of 100–2000) provide insights into thermal profiles, fluid temperature distributions, and flow configurations within the SCHE. Staggered arrangement and gap spacing are employed to reduce pressure loss and enhance airflow strength. The results highlight flow structures and heat transfer characteristics in the heat exchanger channels, elucidating the underlying mechanisms of the heat exchange process. Understanding these behaviors is crucial for developing more efficient heat exchangers and vortex generators in the future. Simulation findings demonstrate that SVTs significantly enhance convective heat transfer over smooth channels due to increased vortex strength. Notably, pattern no. 2 SVTs (b1/H = b2/H = 0.20) achieve the highest Nu/Nu0 of 19.21 in the +x flow direction at Re = 2000, α = 30°, and P/H = 1. In conclusion, the study identifies a maximum thermal enhancement factor of 4.38. It underscores the potential of pattern no. 2 SVTs for optimizing heat exchanger performance, offering valuable insights for future developments in thermal management technologies.
Keywords: CFD; Heat exchanger; Square channel